Utilization of leonardite, flue gas desulfurization gypsum and clay for production of ceramic plant growth material - Srisomang,R. (Springer Verlag, 2015)
© 2014, Springer-Verlag Berlin Heidelberg. The commercial plant growth materials are widely used in a soil-less culture because of their high hardness and ease of use. However, the disadvantages of commercial plant growth materials are expensive because of low density and high pH value. The objective of this research is to produce ceramic plant growth material (CPGM) from leonardite and flue gas desulfurization (FGD) gypsum, which are residues from a coalmine and electric power plant in Lampang province, Thailand, mixed with clay and sawdust. The optimal ratio of these constituents combined with clay was determined, using sawdust residue as an additive. The effect of different quantities of sawdust addition on the properties of CPGM was investigated. The mixtures were formed and fired at 500, 600, 650, 700 and 800 °C, respectively. It was found that the weight ratio of 58 % leonardite, 17 % FGD gypsum and 8 % clay with 17 % sawdust mixed; firing at 650 °C were the most suitable conditions for production of CPGM. The resulting CPGM did not slake when soaked in water having 61.7 % water absorption, 75.5 % apparent porosity, pH value around 6.4, apparent density of 3.26 g/mL, bulk density of 1.39 g/mL, CEC value of 19.2 meq/100 g and surface area of 57.2 m2/g. Furthermore, the results from Barrett-Joyner-Halenda analysis showed that the produced CPGM was mesoporous material which has an average pore size of 7.12 nm and 89 % mesopores.